Characterisation of wood growth regions by multivariate analysis of ToF‐SIMS data. (8th December 2015) - Trindade, Gustavo F.; Bañuls‐Ciscar, Jorge; Ezeh, Clive K.; Abel, Marie‐Laure; Watts, John F.
Abstract : This work presents a methodology to characterise the surface of Scots pine wood samples cut at different geometries by performing principal component analysis and non‐negative matrix factorisation (NMF) of ToF‐SIMS data. With the aid of two standard samples of lignin organosolv and cellulose, the NMF results reduced the data to two compounds which are representative of the surface coverage of lignin and cellulose. Differences between the relative amounts of lignin and cellulose in early and late wood were in agreement to the anatomy of wood, making the multivariate analysis a potential way to differentiate species and potentially ages of the wood in terms of their natural components. Copyright © 2015 John Wiley & Sons, Ltd.